Local vs global heat transfer and flow analysis of hydrocarbon complete condensation in plate heat exchanger based on infrared thermography. (November 2015) - Sarraf, K.; Launay, S.; El Achkar, G.; Tadrist, L.
Highlights: Two-phase flow distribution in plate heat exchanger based on IR visualization. Identification of condensation characteristics ( x, htp, q ) along the heat exchanger. Identification of gravitational and transitional regimes depending on mass flux. Underestimation of h ‾ tp based on literature assumptions compared to IR results. Similarity in flow behavior between homogeneous and Lockhart–Martinelli models. Abstract: Plate heat exchangers (PHE), compact and energy-efficient, are used as condensers in various industrial applications to recover and recycle heat energy. The condenser optimization still represents a challenge. Due to complex thermo-hydraulic couplings inside three-dimensional PHE geometry, most of the literature studies are correlatives based on hypothesis as uniform heat flux or heat transfer coefficient along the condenser. In this article, some new information on the analysis of condensation heat transfer along the PHE is highlighted. The experimental study focuses on complete condensation of saturated pentane inside a PHE of 4.4 mm hydraulic diameter placed vertically with a descending flow of the refrigerant. The global and local thermo-hydraulic characteristics, as the vapor quality, the heat flux density and the heat transfer coefficient, were identified along the PHE based on the infrared thermography, and the effect of mass flux, between 9 and 30 kg m −2  s −1, on these characteristics is analysed. The results show a significant variation, of the heat transfer coefficient and the heat flux density, between the inlet and the outlet of the condensation region for most of the mass fluxes. In our operating range, the heat flux rate decreases till 400% between the PHE inlet and outlet, while the condensation heat transfer coefficient decreases by 5–10 times. The PHE mean heat transfer coefficients, calculated from the local values are then 10–20% higher than the ones calculated from the literature assumption of uniform heat fluxes or the assumption of constant heat transfer coefficient. Moreover, the variation of the mean heat transfer coefficient with pentane mass flux allowed the identification of two condensation regimes, from gravity mode to a mix gravity/convection mode, with a transition limit around 15 kg m −2  s −1 . Condensation flow analysis was conducted based on pressure drop measurements and calculations. Hence the global pressure drop measured experimentally and the local profile deduced from infrared images, are compared to the results obtained by models from the literature. The comparison shows that the homogeneous model and the Lockhart–Martinelli (1949)'s model predict with good agreement the experimental results.